LEADERSHIP AND TEAM PERFORMANCE AS DEVELOPMENT TOOL FOR CREATING SUSTAINABLE EDUCATION - Kvelde, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Team performance is important at work and in organizational psychology as it aims to promote human energy. The human energy is more than just a “New Age” concept, it has a substantial and predictable effect on performance and innovation in organizations. The aim of the study is to examine relations between leadership style and team performance and mediating role is played by the productive organizational energy. The study is based on literature and quantitative and qualitative research methods. A theoretical framework is assessed in the empirical study in Latvian organizations in 2019. The study was accomplished in co-operation with America company "The Energy Project" and the University of Arizona. The article reveals the model of human energy as a scientifically-based approach and transformational leadership as a development tool, which already has spread in all sectors of western societies, including educational organizations. The materials and recommendations can be used to assist organizations in identifying practices, processes and initiatives, which can have a positive impact on team performance and organizational energy. The general conclusion is that the transformation leadership lays a positive dynamic in the development of the team performance for sustainable education. The educational organizations can progress productive performance and create sustainable education in a particular manner by focusing on their human resources; considering their growth, development and well-being.